Evaluasi Cepat Desain Elemen Balok Beton Bertulangan Tunggal Berdasarkan Rasio Tulangan Balanced - Agus Setiawan (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Design procedure for reinforced concrete structure in Indonesia is provided by “Tata Cara Perhitungan Struktur Beton, SNI 03-2847-2002”. This code covers analysis method and basic assumptions that can be taken by a structural designer to design a reinforced concrete structure. An engineer has to design a flexural component, one of the structural component. One of the flexural component is beam element. SNI 03-2847-2002 adopt capacity design menthod in beam element design. This paper will be discuss a simple design procedure in beam element, based on  variabel, which is ratio between /b, with b is the balanced reinforcement ratio. The  value is limited to 0,75 maximum in SNI 03-2847-2002. A dactail failure is guarantee in a beam element with  under 0,75. The analysis that have been done before, produce the correlation between Mn/bd2 and which can be a tool for design a beam element. A simple calculation use the table (Mn/bd2 vs ) will be present at the end of this paper.